Age of onset of myopia predicts risk of high myopia in later childhood in myopic Singapore children - Chua, Sharon Y. L.; Sabanayagam, Charumathi; Cheung, Yin-Bun; Chia, Audrey; Valenzuela, Robert K.; Tan, Donald; Wong, Tien-Yin; Cheng, Ching-Yu; Saw, Seang-Mei (Ophthalmic & physiological optics, 2016)
Purpose To investigate the effect of age of myopia onset on the severity of myopia later in life among myopic children. Methods In this prospective study, school children aged 7–9 years from the Singapore Cohort Of the Risk factors for Myopia (SCORM) were followed up till 11 years (n = 928). Age of myopia onset was defined either through questionnaire at baseline (age 7–9 years) or subsequent annual follow‐up visits. Age of onset of myopia was a surrogate indicator of duration of myopia progression till age 11 years. Cycloplegic refraction and axial length were measured at every annual eye examination. High myopia was defined as spherical equivalent of ≤−5.0 D. A questionnaire determined the other risk factors. Results In multivariable regression models, younger age of myopia onset (per year decrease) or longer duration of myopia progression was associated with high myopia (odds ratio (OR) = 2.86; 95% CI: 2.39 to 3.43), more myopic spherical equivalent (regression coefficient (β) = −0.86 D; 95% CI: −0.93 to −0.80) and longer axial length (β = 0.28 mm; 95% CI: 0.24 to 0.32) at aged 11 years, after adjusting for gender, race, school, books per week and parental myopia. In Receiver Operating Curve (ROC) analyses, age of myopia onset alone predicted high myopia by 85% (area under the curve = 0.85), while the addition of other factors including gender, race, school, books per week and parental myopia only marginally improved this prediction (area under the curve = 0.87). Conclusions Age of myopia onset or duration of myopia progression was the most important predictor of high myopia in later childhood in myopic children. Future trials to retard the progression of myopia to high myopia could focus on children with younger age of myopia onset or with longer duration of myopia progression.